The feasibility of task-sharing the identification, emergency treatment, and referral for women with pre-eclampsia by community health workers in India - Umesh Charanthimath; Marianne Vidler; Geetanjali Katageri; Umesh Ramadurg; Chandrashekhar Karadiguddi; Avinash Kavi; Anjali Joshi; Geetanjali Mungarwadi; Sheshidhar Bannale; Sangamesh Rakaraddi; Diane Sawchuck; Rahat Qureshi; et al. (BMC, 2018)
Abstract Background Hypertensive disorders are the second highest direct obstetric cause of maternal death after haemorrhage, accounting for 14% of maternal deaths globally. Pregnancy hypertension contributes to maternal deaths, particularly in low- and middle-income countries, due to a scarcity of doctors providing evidence-based emergency obstetric care. Task-sharing some obstetric responsibilities may help to reduce the mortality rates. This study was conducted to assess acceptability by the community and other healthcare providers, for task-sharing by community health workers (CHW) in the identification and initial care in hypertensive disorders in pregnancy. Methods This study was conducted in two districts of Karnataka state in south India. A total of 14 focus group discussions were convened with various community representatives: women of reproductive age (N = 6), male decision-makers (N = 2), female decision-makers (N = 3), and community leaders (N = 3). One-to-one interviews were held with medical officers (N = 2), private healthcare OBGYN specialists (N = 2), senior health administrators (N = 2), Taluka (county) health officers (N = 2), and obstetricians (N = 4). All data collection was facilitated by local researchers familiar with the setting and language. Data were subsequently transcribed, translated and analysed thematically using NVivo 10 software. Results There was strong community support for home visits by CHW to measure the blood pressure of pregnant women; however, respondents were concerned about their knowledge, training and effectiveness. The treatment with oral antihypertensive agents and magnesium sulphate in emergencies was accepted by community representatives but medical practitioners and health administrators had reservations, and insisted on emergency transport to a higher facility. The most important barriers for task-sharing were concerns regarding insufficient training, limited availability of medications, the questionable validity of blood pressure devices, and the ability of CHW to correctly diagnose and intervene in cases of hypertensive disorders of pregnancy. Conclusion Task-sharing to community-based health workers has potential to facilitate early diagnosis of the hypertensive disorders of pregnancy and assist in the provision of emergency care. We identified some facilitators and barriers for successful task-sharing of emergency obstetric care aimed at reducing mortality and morbidity due to hypertensive disorders of pregnancy.